Diversi Oleh Pengadilan Negeri Kotabumi Sebagai Bentuk Penyelesaian Perkara Anak - Mardianto, Andi Barkan; Idham, Idham; Purwoko, Tedy; Santina, Rika (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Furthermore, the Children's Judge in its implication has an obligation and realizes a balanced Diversity Agreement for both parties, in which the agreement of diversia is an agreement on the results of the Diversion deliberation process as outlined in the form of documents and signed by the parties involved in the Diversion deliberation. handling children as perpetrators of crime is one form of attention of judges to the conditions of children who are different from adults, the nature of children as individuals who are still unstable, the future of children as assets of the nation and the position of people in communities who still need protection can be used as a basis for searching alternative solutions on how to avoid children from a formal criminal justice system. The method used in this study is an empirical approach derived from data collection obtained from primary data and secondary data, then analyzed by qualitative analysis methods. The results of this study ultimately provide the answer that diversion as a form of settlement of child criminal cases through the Restorative justice approach by Judges of Children in the Kotabumi District Court can be implicated because of observing 1) The best interests of the Child, 2) The survival and growth of the Child. The suggestion from this research is that the role of the Facilitator needs to be socialized more intensively to the community because there are still many people who do not understand correctly the implementation of diversion.